Severe SARS‐CoV‐2 infection presenting with acute kidney injury and diabetic ketoacidosis complicated by pancreatitis in a 53‐year man with hypertension - Elrazi Ali (14777284) (2023)
Severe COVID-19 infection is associated with significant stress and marked immune response that can affect many organs and precipitate DKA, pancreatitis, and acute renal injury, which might be permanent. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.3731